Revitalisasi Pendidikan Sains Sebagai Pilar Pembentukan Kompetensi Adaptif dan Kritis: Sebuah Systematic Literature Review - I Kadek Aditia Putra; I Wayan Suastra; Ida Bagus Putu Arnyana; I Made Citra Wibawa (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to explore the role of science education in developing students’ critical thinking and adaptability in facing the challenges of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era and Society 5.0. The method used was a Systematic Literature Review (SLR) by analyzing 20 primary articles published between 2020 and 2024 and indexed in reputable databases, namely Scopus and Sinta. The results identified four main strategies for developing critical and adaptive skills: (1) positioning students as verifiers of knowledge through Argument-Driven Inquiry, (2) training students to manage uncertainty through socio-scientific issues, (3) building mental resilience through technology-based simulations, and (4) strengthening metacognitive aspects. In conclusion, science education should be positioned not only as a subject but also as a means of developing students’ mental resilience in facing uncertainty. Keywords: Adaptability, Critical Thinking, 21st Century Competencies, Science Education, Systematic Literature